Dynamic impact of banking performance on financial stability: Fresh evidence from Southeastern Europe - Veton Zeqiraj; Flamur Mrasori; Omer Iskenderoglu; Kazi Sohag (Journal of Central Banking Theory and Practice, 2021)
This study addresses the issue of whether banking performance impacts financial stability in Southeastern European countries. To answer this question, the GMM approach has been applied in the analyses of the panel data over the period 2000-2015 for Southeastern Europe. The findings reveal the presence of significant positive long-run relationship between ROA, ROE, trade openness, and human capital, while government expenditures have negative impact on financial stability. Trade openness, human capital and government expenditures can keep the financial system stable as a whole. The Granger causality analysis discloses the main hypothesis where the banking system in this part of Europe accounts for more than 80% of the financial system. The study sheds light to the policymakers and research about the role of banking performance on financial stability for this region of Europe.
Keywords: B26; G2; G3; O1; O2; 330; Financial stability; Banking performance; Generalized Method of Moments; Southeastern Europe